Thomas Adams in Canada, 1914-1930 - Simpson, Michael (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1982)
Thomas Adams (1871-1940), a leading British planning pioneer, became planning adviser to the Commission of Conservation in 1914. Galvanizing the infant Canadian planning movement, he gave it a comprehensive legislative, institutional and professional structure by 1919. Like his hosts, he was a utilitarian, a meliorist and a functionalist. His system broke down in the 1920s when the atmosphere was not congenial for planning and Canadian society too immature to accept his message. Little of his actual structure now survives but Canadian planning philosophy remains essentially utilitarian. This article discusses Adams's British background, his aims and policies in Canada, his successes and failures and his significance in Canadian planning history.